2020
DOI: 10.1063/5.0024127
|View full text |Cite
|
Sign up to set email alerts
|

Determining the radial distribution function of water using electron scattering: A key to solution phase chemistry

Abstract: High energy electron scattering of liquid water (H 2 O) at near-ambient temperature and pressure was performed in a transmission electron microscope (TEM) to determine the radial distribution of water, which provides information on intra-and intermolecular spatial correlations. A recently developed environmental liquid cell enables formation of a stable water layer, the thickness of which is readily controlled by pressure and flow rate adjustments of a humid air stream passing between two silicon nitride (Si 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 77 publications
8
16
0
Order By: Relevance
“…Finally, we demonstrated that UED is sensitive to both electronic and nuclear dynamics, not only to structural changes. This point was also made recently by de Kock et al…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we demonstrated that UED is sensitive to both electronic and nuclear dynamics, not only to structural changes. This point was also made recently by de Kock et al…”
Section: Discussionsupporting
confidence: 77%
“…The RDF between oxygen–oxygen pairs of two water molecules (Figure S2) is similar to literature profiles and shows a sharp peak at 2.75 Å (Table ) for all three simulation setups. This value is close to the expected average hydrogen bond length in water, 2.8 Å . In addition, all RDFs between two identical species (not showed) are found to be independent of the particle composition as expected for such dilute systems.…”
Section: Model Validationsupporting
confidence: 84%
“…This value is close to the expected average hydrogen bond length in water, 2.8 Å. 161 In addition, all RDFs between two identical species (not showed) are found to be independent of the particle composition as expected for such dilute systems.…”
Section: Model Validationmentioning
confidence: 99%
“…It is crucial to keep in mind that the measured temperature presented in this work does not directly relate to the liquid temperature itself but reflects the temperature of the embedded Au nanoparticles. Although solvent temperature would be theoretically accessible by electron scattering, as well, 48 the vast majority of LPTEM experiments aims at analyzing processes of nanostructures enclosed in the liquid rather than studying the liquid itself. Thus, the temperature of the nanocrystals is particularly interesting for practical considerations.…”
Section: Discussionmentioning
confidence: 99%